1) 4(5х + 2) = 10(3х – 3) + 15

2) 2(7х – 7) = 7(2х – 3) + 7

3) 5,6 – 3(2 – 0,4х) = 0,4(4х – 1)

4) 5(х – 12) = 6(х – 10) – х

5) 0,3(8 – 3у) = 3,2 – 0,8(у – 7)

6) 4(х – 1) = 2(2х – 8) + 12

7) 8(5 – 3х) = 6(2 – 4х) + 7

8) 7(4х – 1) = 6 – 2(3 – 14х)

Шамшербек Шамшербек    1   21.04.2020 13:50    0

Ответы
RitkaRita RitkaRita  22.04.2020 06:30

1)

4(5х+2)=10(3х-3)+15

20х+8=30х-30+15

8+30-15=30х-20х

23=10х

х=23:10

х=2,3

2)

2(7х-7)=7(2х-3)+3

14х-14=14х-21+3

14х-14х=-21+3+14

0х=-4

нет решения

3)5.6-3(2-0.4х)=0.4(4х-1)

5.6-6+1,2х=1,6х-0.4

5.6-6+0.4=1.6х-1.2х

0=0.4х

х=0

4)

5(х-12)=6(х-10)-х

5х-60=6х-60-х

-60+60=5х-5х

0=0

х может быть любым.

5)

0,3(0-3у)=3,2-0.8(у-7)

0-0.9у=3.2-0.8у+5.6

0-3.2-5.6=-0.8у+0.9у

-8.8=0.1у

у=-88

6)

4(х-1)=2(2х-8)+12

4х-4=4х-16+12

4х-4х=-4+4

0=0

х может быть любым.

ПОКАЗАТЬ ОТВЕТЫ
reventon1 reventon1  22.04.2020 06:30

1 20х+8=30х-30+15

 20х-30х=-15-8

-10х=-23

 х=2,3

2 2*[-49]=14х-21+7

  -98=14х-14

 х=-6

3  5,6 - 6 + 1,2х = 0,4(4x + 1) ;  

   -0,4 + 1,2х = 1,6x + 0,4 ;  

   1,2х - 1,6х = 0,4 + 0,4 ;

   -0,4х = 0,8 ;

х = -2;

4 5x-60=6x-60-x

5x-6x+x=60-60

0=0

5  0,3*(8-3у)=3,2-0,8(у-7)

2,4-0,9у=3,2-0,8у+5,6

2,4-3,2-5,6=0,9у-0,8у

2,4-8,8=0,1у

-6,4=0,1у

у=-6,4:0,1

у=-64

6  4 (х-1)=2(2х-8)+12

4x - 4 = 4x - 16 + 12

4x - 4 =  4x - 4

x может быть любым

7 40-24х=12-24х+7

40-24х=-24х+19

-24x+24x=19-40

Тогда получается 0=-21

корней нет

8 28х-7=6-6+28х

0=7

корней нет

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика